SYSTEM ADMINISTRATION BUILDING SEMINAR RENTAL BALAI PRAJURIT ARDHYA GARINI - Heru Kuncoro; Erick Orlando SKom, MMSI (Jurnal Sistem Informasi, 2006)
The development of more sophisticated computer very helpful in data processing still using manual systems. This is often menimbulakan issues related to the accuracy of the data that caused delays in data processing. The information is valuable information quickly and accurately. Then needed a computerized system as supporters. SistemAdministrai Rental Center Building Seminar on Private Garini Ardhya Ardhya Garini Foundation designed with the aim to obtain and process information quickly and accurately as well as secure data storage. So that the final results are useful in decision making.